Characterization of the Alternative Sigma Factor σ(54) and the Transcriptional Regulator FleQ of Legionella pneumophila, Which Are Both Involved in the Regulation Cascade of Flagellar Gene Expression - Jacobi, Sebastian (American Society for Microbiology, 2004)
We cloned and analyzed Legionella pneumophila Corby homologs of rpoN (encoding σ(54)) and fleQ (encoding σ(54) activator protein). Two other genes (fleR and pilR) whose products have a σ(54) interaction domain were identified in the genome sequence of L. pneumophila. An rpoN mutant strain was nonflagellated and expressed very small amounts of the FlaA (flagellin) protein. Like the rpoN mutant, the fleQ mutant strain of L. pneumophila was also nonflagellated and expressed only small amounts of FlaA protein compared to the amounts expressed by the wild type. In this paper we show that the σ(54) factor and the FleQ protein are involved in regulation of flagellar gene operons in L. pneumophila. RpoN and FleQ positively regulate the transcription of FliM and FleN, both of which have a σ(54)-dependent promoter consensus sequence. However, they seemed to be dispensable for transcription of flaA, fliA, or icmR. Our results confirmed a recently described model of the flagellar gene regulation cascade in L. pneumophila (K. Heuner and M. Steinert, Int. J. Med. Microbiol. 293:133-145, 2003). Flagellar gene regulation was found to be different from that of Enterobacteriaceae but seems to be comparable to that described for Pseudomonas or Vibrio spp.